2020
DOI: 10.3390/su12187627
|View full text |Cite
|
Sign up to set email alerts
|

Abandoned Places and Urban Marginalized Sites in Lugoj Municipality, Three Decades after Romania’s State-Socialist Collapse

Abstract: The postsocialist process of urban restructuring came with important spatial, social, and economic consequences. This triggered important transformations that remain palpable in the everyday texture of urban life, spatial patterns, and even the internal structures of the city. Every urban settlement was bound to contribute to the state socialist industry so that postsocialist urban transformations also included multiple aspects of dereliction and ruination of the socialist industrial assets. Threatening postso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 81 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…This revealed that the city is sprawling at a significant pace. The gross population density of Lahore was 4883 persons per km 2 and 6279 persons per km 2 in the year 2010 and 2017, respectively, which was well short of the recommended standard of the UN-Habitat. The recommended density for compact development is at least 15,000 km 2 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…This revealed that the city is sprawling at a significant pace. The gross population density of Lahore was 4883 persons per km 2 and 6279 persons per km 2 in the year 2010 and 2017, respectively, which was well short of the recommended standard of the UN-Habitat. The recommended density for compact development is at least 15,000 km 2 .…”
Section: Discussionmentioning
confidence: 73%
“…Four sub-indicators, namely, gross population density, built-up area density, land use breakup, and average land consumption per capita were considered to comprehend the density pattern. It is recommended that the population density within a sustainable neighborhood should be at least 15,000 persons per km 2 (150 persons/ha) [48]. The gross population density of Lahore was 4883 persons per km 2 and 6279 persons per km 2 in 2010 and 2017, respectively.…”
Section: Density Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of accounting for the facilities with different characteristics is not just applied to housings in ordinary status. Space rearrangement is certainly required for the prominent change in the new political, economic, social, and cultural state and in its major spatial shifts occurred in the urban restructuring processes [20,21] framing a foundation for the study here to focus on the evaluation of the specific concerned targets in one of the municipalities in Taiwan.…”
Section: Introductionmentioning
confidence: 99%